Can main group systems act as superior catalysts for dihydrogen generation reactions? A computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Dalton Transactions, 2016)
The protolytic cleavage of the O-H bond in water and alcohols is a very important reaction, and an important method for producing dihydrogen. Full quantum chemical studies with density functional theory (DFT) reveal that germanium based complexes, such as HCCMeArB(2)GeH (Ar = 2,6-(Pr2C6H3)-Pr-i), with the assistance of silicon based compounds such as SiF3H, can perform significantly better than the existing state-of-the-art post-transition metal based systems for catalyzing dihydrogen generation from water and alcohols through the protolysis reaction.